Pengaruh Ukuran Perusahaan, Umur Perusahaan, dan Opini Audit terhadap Ketepatan Waktu Penyampaian Laporan Keuangan: Studi Empiris pada Perusahaan Sektor Consumer Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024 - Yendri, Zarefa; Deviani, Deviani (Jurnal Eksplorasi Akuntansi, 2025)
Examining the impact of the company's age, size, and audit opinion of the timeliness of financial statement submission in consumer cyclicals businesses that are listed on the Indonesia Stock Exchange is the aim of this research. The study population consists of companies from the consumer cyclicals sector listed between 2022 - 2024. Purposive sampling was used to choose 94 companies as samples. The research relies on secondary data collected from company websites and other relevant platforms. The analytical method employed is logistic regression. The findings demonstrate that company size and age do not significantly influence timely reporting, while audit opinion exerts a significant positive effect.